Análisis de la velocidad y la aceleración entre un golpe de boxeo y uno de taekwondo - Sánchez-Rodriguez, D. A.; Bohórquez-Aldana, A. F. (Revista U.D.C.A Actualidad & Divulgación Científica, 2020)
Within the national and international scope, studies that assess the similarity or difference between the main knock of combat sports will be seen. For this reason, the maims of this research is to analyze the most representative knock of Boxing and Taekwondo, pretent to recognice the differences between the speed and acceleration of the execution of the straight punch in boxing and the chagi bandal in the taekwondo. The method used was observational, cross-sectional and descriptive. It was processed by the video capture of the straight strokes and chagi bandal, it was analyzed by means of the Ehuman software version 5.0. The statistical procedure involved a Mann Whitney U Test to determine the similarity or difference between the variables. The sample was conformed by 8 boxers and 8 takwondo athletes from the male category of Bogotá, who had part of the capital's performance teams. Among the results affected, the difference between speeds of the straight punch in boxing, corresponding to 4.17 ± 1.35 m/s, was highlighted, compared to the bandal chagi kick of 11.75 ± 1.04 m/s, the difference statistic was p = 0.0008. For the evaluation of the acceleration the straight hit, the following results are shown, 12.3 ± 5.41m/s2, while the bandal chagi kick had an average result of 74 ± 37.85m/s2, the statistical difference was of p = 0.00033 using a significance level of p = 0.05 for the measurements.